Empowering Local Voices: Transforming Valu Beach into a Sustainable Tourism Destination - Setiyarti, Tettie; Gonzaga, Marciana; Trisna Wijayanthi, Ida Ayu; Oka Pradnyana, I Gusti Gede; Pradnya Handayani, Sagung Agung Diah (Greenation Research & Yayasan Global Resarch National, 2024)
Local community empowerment is essential for sustainable tourism development, enabling communities to actively participate in tourism planning and management. This article examines the role of community participation in the development of Valu Beach in Pitileti Village, Lautem District, Timor-Leste. Employing qualitative descriptive analysis, the study reveals that local engagement is vital for maximizing economic and social benefits while preserving the environment. Despite existing challenges, such as limited accessibility and a lack of tourism management skills, community enthusiasm indicates a strong desire for involvement. The research highlights the importance of enhanced infrastructure, targeted training, and government support to foster a collaborative approach. By leveraging local assets, ie. natural beauty, cultural richness, and community spirit, Valu Beach can emerge as a sustainable tourism destination, benefiting both the community and visitors alike.